2021
DOI: 10.3390/informatics8020026
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Governance for Higher Education Institutions: A Multi-Country Study

Abstract: Information Technology governance (ITG) calls for the definition and implementation of formal practices at the highest level in the organization, involving structures, processes and relational practices for the creation of business value from IT investments. However, determining the right ITG practices remains a complex endeavor. Previous studies identify IT governance practices used in the health and financial sectors. As universities have many unique characteristics, it is highly unlikely that the ITG experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
(90 reference statements)
0
16
0
1
Order By: Relevance
“…Therefore, ITG management still has a long way to go. All recent academic literature studies in the field of ITG within universities [22], [49]- [55] pact of ITG on performance and strategic alignment. The obtained results from their analysis have not provided a clear vision of the adoption of an ITG framework in HEIs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ITG management still has a long way to go. All recent academic literature studies in the field of ITG within universities [22], [49]- [55] pact of ITG on performance and strategic alignment. The obtained results from their analysis have not provided a clear vision of the adoption of an ITG framework in HEIs.…”
Section: Resultsmentioning
confidence: 99%
“…Given the large number of these committees, defining their roles and responsibilities is essential to avoid overlapping decisions and make them more efficient (Bianchi et al, 2020). Addo et al (2021); Soobaroyen et al (2019) consider the audit committee and risk management as an effective tool for achieving strategic objectives Structure of the IT organization (S4): According to Scalabrin Bianchi et al (2021), the federal mode is the most adopted by large and huge universities. On the other hand, the centralized structure is adopted by mediumsized universities.…”
Section: Structurementioning
confidence: 99%
“…It is necessary to define the skills and experiences the expectations of the leaders of higher education of the CIOs for more efficiency of ITG (Dlamini, 2015). On the other hand, Scalabrin Bianchi et al (2021) have shown the effectiveness of two good practices of project management offices (S6) and business process management offices (S7) in universities in Germany, Brazil, Portugal and Spain.…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…COBIT is the most widely adopted IT Governance framework (Smits & Hillegersberg, 2018). COBIT has been designed with established best practices in the field of IT governance in mind (Scalabrin Bianchi et al, 2021). It aids companies by aligning their IT assets and processes with their business objectives (Santos Castellanos, 2020).…”
Section: Introductionmentioning
confidence: 99%